(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
The pension system, together with the social assistance services form the social security system is recognized worldwide throughout the adoption of the Universal Declaration of Human Rights for the purpose of insured person compensation for damages regarding some inherent risks as: permanent or temporary inability of work, old age or unemployment. The main objectives of a pension system are decreasing poverty regarding the lower income persons throughout the conditions of limitation of the working capacity which are financially vulnerable. In this article we provide a qualitative and quantitative overview regarding the Romanian pension system structure and mechanism. The conclusions of this article highlight the need for a more comprehensive reform of this system in order to strengthen it for the new challenges still to come in the near future.